Use of defatted cottonseed-derived biochar for biodiesel production: a closed-loop approach - Gyeongnam Park; Jonghyun Park; Jee Young Kim; Doyeon Lee; Eilhann E. Kwon (Biochar)
Abstract This study aimed to enhance the economic viability and sustainability of the cotton industry by converting cottonseed into energy. Cottonseed was subjected to lipid extraction for biodiesel production, and a pyrolysis test was conducted under N2 and CO2 conditions to valorise defatted cottonseed. Under CO2 conditions, the increase in CO concentration was due to homogeneous reaction of CO2 with volatile matters. Biochar, a pyrolytic product of defatted cottonseed, was used as a catalyst for thermally induced transesterification, and showed high performance in biodiesel conversion efficiency due to its abundant alkaline earth metals and meso-/macro-pores. For example, transesterification using silica at 250 ˚C yielded only 1.6 wt.% biodiesel, whereas using biochar at the same temperature resulted in a significantly higher biodiesel yield of 83.5 wt.%. This study experimentally proved that 7,900 tons (304 million MJ) of biodiesel could be produced annually, surpassing the diesel fuel requirement (145 million MJ) for cotton cultivation. These results indicate the potential to fully replace fossil fuels in the cotton industry. Graphical Abstract